An increase in the rate of global mean sea level rise since 2010. Issue 10 (21st May 2015) - Yi, Shuang; Sun, Wenke; Heki, Kosuke; Qian, An
Abstract The global mean sea level (GMSL) was reported to have dropped 5 mm due to the 2010/2011 La Niña and have recovered in 1 year. With longer observations, it is shown that the GMSL went further up to a total amount of 11.6 mm by the end of 2012, excluding the 3.0 mm/yr background trend. A reconciled sea level budget, based on observations by Argo project, altimeter, and gravity satellites, reveals that the true GMSL rise has been masked by El Niño–Southern Oscillation‐related fluctuations and its rate has increased since 2010. After extracting the influence of land water storage, it is shown that the GMSL has been rising at a rate of 4.4 ± 0.5 mm/yr for more than 3 years, due to an increase in the rate of both land ice loss and steric change.